2021
DOI: 10.1038/s41467-021-25515-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the expanding phenotypic spectrum of inherited disorders of biogenic amines

Abstract: Inherited disorders of neurotransmitter metabolism are rare neurodevelopmental diseases presenting with movement disorders and global developmental delay. This study presents the results of the first standardized deep phenotyping approach and describes the clinical and biochemical presentation at disease onset as well as diagnostic approaches of 275 patients from the registry of the International Working Group on Neurotransmitter related Disorders. The results reveal an increased rate of prematurity, a high ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
(66 reference statements)
0
33
1
Order By: Relevance
“…In order to distinguish the initial presentation and the evolving clinical phenotypes of rare diseases, comparative phenotyping within and between disease groups is a helpful strategy. Recently, this approach was successfully applied to elucidate clinical similarities and differences between disorders of biogenic amine and tetrahydrobiopterin (BH 4 ) metabolism ( 37 ), urea cycle disorders, and organic acidurias ( 24 ). This knowledge is of relevance for the optimization of the diagnostic process, patient clinical paths, healthcare planning, and counselling of parents having a child with a rare disease.…”
Section: Patient Registries Are Multi-purpose Instruments For Rare Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to distinguish the initial presentation and the evolving clinical phenotypes of rare diseases, comparative phenotyping within and between disease groups is a helpful strategy. Recently, this approach was successfully applied to elucidate clinical similarities and differences between disorders of biogenic amine and tetrahydrobiopterin (BH 4 ) metabolism ( 37 ), urea cycle disorders, and organic acidurias ( 24 ). This knowledge is of relevance for the optimization of the diagnostic process, patient clinical paths, healthcare planning, and counselling of parents having a child with a rare disease.…”
Section: Patient Registries Are Multi-purpose Instruments For Rare Di...mentioning
confidence: 99%
“…Furthermore, these studies described a so far unknown renal disease manifestation, unraveled similarities (risk of striatal necrosis with concomitant complex movement disorder with predominant dystonia) and discrepancies (cognitive function, white matter changes, subdural hematoma) between biochemically delineated subgroups (high versus low excreter phenotype), and evaluated which part of the complex clinical spectrum can be specifically targeted and changed by current therapy, highlighting the need for safer and more effective medicines. Similar approaches to continuous improvement of guidelines for rare diseases through long-term observational studies coordinated by international scientific consortia have also been chosen for other rare diseases, such as urea cycle disorders ( 70 , 71 ), propionic and methylmalonic aciduria ( 72 , 73 ), cobalamin-related remethylation disorders ( 74 76 ), cystathionine beta-synthase deficiency ( 41 , 77 ), and neurotransmitter-related disorders ( 37 , 78 , 79 ).…”
Section: Patient Registries Are Multi-purpose Instruments For Rare Di...mentioning
confidence: 99%
“…Besides GA1, this iterative approach of longitudinal observational studies conducted by international scientific consortia and concomitant guideline development is also successfully applied to other IMDs, such as methylmalonic and propionic aciduria, 53,[94][95][96] urea cycle disorders, 57,58,97 cystathionine beta-synthase deficiency, 98 remethylation disorders, 54,99,100 and tetrahydrobiopterin deficiencies. 56,101 The GA1 example also highlights another important aspect for guiding future extension strategy for NBS programs. Without inclusion of GA1 to NBS pilot studies or NBS programs before having ample evidence that it is a treatable condition the above-described success story would have been inconceivable if not impossible.…”
Section: To Treat or Not To Treat? And How?mentioning
confidence: 99%
“…In practice, the observed THD phenotypes do, however, fit along a spectrum with overlap of both clinical features and TH mutations between the two groups [20]. The recent International Working Group on Neurotransmitter-Related Disorders registry study employed the first standardized deep phenotyping approach with 44 THD patients and concluded that the type A/B classification is not justified and proposed to abandon this classification entirely [21]. Thus, while a categorization based on symptoms may assist clinicians towards achieving more personalized care for different patient cohorts, in the case of THD, such efforts have yielded limited success to date.…”
Section: The Clinical Manifestations Of Thdmentioning
confidence: 99%